2006
DOI: 10.1111/j.1742-7843.2006.pto_230.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Suspected and Challenge‐Verified Penicillin Allergy in a University Hospital Population

Abstract: Suspected penicillin allergy is common among hospitalised patients, but the quality of the information given by the patient is often doubtful. Alleged penicillin allergics are likely to be treated with more toxic, broad-spectered, and more expensive antibiotics, with effects on microbial resistance patterns and public economy as a consequence. We performed a cross-sectional case-control study with two visits to all clinical departments of a large university hospital in order to find in-patients with medical fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
84
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 27 publications
17
84
1
4
Order By: Relevance
“…[10,11] The absence of organized continuing medical education programs and problematic physician attitude are other problems that add to under reporting of the adverse drug reaction. [12] There was predominance of female sex for adverse drug reactions which was similar to a study conducted by Albin S et al 13 The mean age of patients was 38.37 years which was less as compared to another study conducted by Jakob E. Borch et al [14] Amoxicillin and clavulanic acid combination was the most common penicillin causing ADRs. But studies done by Sara et al and Trubiano et al showed amoxicillin alone as most common penicillin causing ADRs.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…[10,11] The absence of organized continuing medical education programs and problematic physician attitude are other problems that add to under reporting of the adverse drug reaction. [12] There was predominance of female sex for adverse drug reactions which was similar to a study conducted by Albin S et al 13 The mean age of patients was 38.37 years which was less as compared to another study conducted by Jakob E. Borch et al [14] Amoxicillin and clavulanic acid combination was the most common penicillin causing ADRs. But studies done by Sara et al and Trubiano et al showed amoxicillin alone as most common penicillin causing ADRs.…”
Section: Discussionsupporting
confidence: 62%
“…Most common system affected was dermatological which was in line with other studies. [13,14] This increased reporting of dermatological ADRs could be due to easy recognition of dermatological reactions than involving other organ systems. [17] Most of the reactions were of probable causality according to WHO criteria since drug rechallenge was not done in any of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two consecutive patients with a self-reported history of an allergic reaction to penicillin on day 2 or later in the course of penicillin treatment referred for routine investigation of penicillin allergy and with negative specific IgE to penicillin G and V, ampicillin and amoxicillin, as well as negative SPT, IDT and DCT were included [3]. All anamnestic reactions were evaluated by the authors and preceded the investigations by more than a year.…”
Section: Methodsmentioning
confidence: 99%
“…In the remaining 64% of patients, a mean of 20 years had passed since the reaction. In these patients, reaction occurred on day 2 or later [3]. A question that needs to be answered is therefore: will more patients react during a DCT if exposed to the suspected penicillin for a longer time, thus improving sensitivity and the predictive values of the entire diagnostic work-up?…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Most do not have either true or persistent allergies, with >90% able to tolerate penicillin after thorough assessment. 1,3 Unnecessary avoidance of penicillin increases health care costs, due to the use of more expensive and/or less effective alternative antibiotics, and contributes to the development of antibiotic resistance. 5,6 Penicillin de-labeling strategies are an increasingly recognized as a valuable component of antibiotic stewardship programs.…”
mentioning
confidence: 99%